The Effects of the Fire Hose Square Knot Browser as a Foraging Enrichment Device on the Behavior of Captive Macaca fascicularis - Puji Rianti; Tamara M. Anisa; Huda S. Darusman (Veterinary Sciences)
Effective management of captive M. fascicularis (long-tailed macaques) is crucial for maintaining high-quality research models, necessitating strategies to promote their welfare. This study evaluated the impact of a foraging enrichment device, the “fire hose square knot browser”, on the behavior of 32 long-tailed macaques at the Primate Research Center of IPB University in Bogor, Indonesia. We observed and analyzed daily behaviors across various food types over 288 h using scan and instantaneous sampling methods. Statistical analyses, including ANOVA and Kruskal–Wallis tests, revealed significant behavioral changes in the presence of the foraging enrichment device. The foraging enrichment device notably increased eating and affiliative behaviors, while reducing resting, agonistic, and stereotypic behaviors. No significant differences in eating, auto-grooming, resting, sexual, agonistic, or stereotypic behaviors were observed between the morning and afternoon. However, mobility and affiliation behaviors varied between these periods. The highest percentage of eating behavior occurred with the enrichment foraging device and a mixture of fruits. Furthermore, a three-way non-parametric analysis suggests a significant effect of food type and treatment on behaviors such as mobility and stereotyping. These findings underscore the positive impact of foraging enrichment devices on promoting active behavior and enhancing animal welfare in captive long-tailed macaques.